Web 2.0: a collaborative learning approach using Edmodo in group discussion - Noor Azlinda, Zainal Abidin; Aisyah Hanum, Abu Bakar; Zuraina, Ali (JHLCB, 2018)
Teaching and learning has become more interactive with the emergence of Web 2.0. Group projects via virtual communication can be done collaboratively and are able to engage students’ participation. These flexibility of time and venue provide convenience to students. This paper aims to explore students’ perceptions towards their communication by using Edmodo in group discussion. It also investigates the students’ attitude towards using Edmodo in completing their group project in the future. The study reveals that students gain benefits in using Edmodo to complete their project and it is one of the best platforms to assist group discussion.